Pengaruh Likuiditas, Efisiensi Aset, dan Struktur Modal terhadap Profitabilitas pada Perusahaan Farmasi Manufaktur di BEI - Julita Julita; M. Edo S. Siregar; Dicky Iranto (International Forum of Researchers and Lecturers, 2026)
The purpose of this study is to analyze the effect of liquidity, asset efficiency, and capital structure on profitability in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange, using Return on Invested Capital (ROIC) as an investment-based profitability indicator. This research employs secondary data from the annual financial statements of pharmaceutical manufacturing companies over a specific period, with multiple linear regression analysis and robust models to ensure model feasibility. The results indicate that liquidity has no effect on profitability. Asset efficiency has a significant negative effect, reflecting the characteristics of the pharmaceutical industry with its high asset intensity. Capital structure has a significant positive effect on profitability, suggesting that measured use of debt can enhance the company’s return on investment. These findings provide theoretical contributions by enriching the literature on investment-based profitability determinants and practical implications for corporate management, investors, and stakeholders in understanding internal factors that influence the financial performance of pharmaceutical companies in Indonesia.